Findings on the feasibility of social pension: Final report - Javier, Roberto E., Jr. (Animo Repository, 2016)
This report contains the findings and the conclusions of the study on the feasibility of a universal social pension in the Philippines. It presents the methodology employed in data generation and its analysis, specifically the strategies used in the conduct of the in-depth group interviews (IGI) at the grassroots and the steps in summarizing the results of the qualitative inquiry using the software NVivo 11 specifically the creation of codes and the formulation of the themes. Attached in this report are the transcripts of the twelve IGI sessions and the NVivo summary of results.